Agricultural developments in Ireland, north and south - Attwood, E. A. (Statistical and Social Inquiry Society of Ireland, 1967)
The agreement on the reduction of the trade barriers between the United Kingdom and the Republic of Ireland has given rise to hopes of a new impetus to the development of Irish agriculture. Economic history is not reversible and no trade agreement could re-create the same precise relationships between the agriculture of Southern and Northern Ireland in 1966 that existed in 1926, but closer trade and economic ties will make the current farming trends in Northern Ireland of much greater significance to the rural community in the rest of Ireland than has been the case in recent years.
Read before the Society, 25 November 1966
Keywords: Irish agriculture; Productivity in Irish agriculture; Agricultural prices; Northern Ireland agriculture; 314.15